An approach to characterizing spatial aspects of image system blur. (25th February 2021) - Adams, Jesse; Pillow, Jessica; Joyce, Kevin; Brennan, Michael; Español, Malena I.; Morzfeld, Matthias; Breckling, Sean; Champion, Daniel; Clarkson, Eric; Coffee, Ryan; Gehring, Amanda; Lund, Margaret; et al.
Abstract: Quantitative X‐ray radiographic imaging systems that utilize a charged couple device (CCD) camera connected to a thick, monolithic scintillator can exhibit blur that varies spatially across the field of view, especially for thick scintillators used in pulse‐power radiography of dynamically compressed objects. A three‐point approach to estimating and accounting for this effect is demonstrated by (a) using a local estimation technique to measure the effect of blurring a calibration object at key locations across the field of view, (b) combining each of the local estimates into a spatially varying blurring function via partitions of unity interpolation, and (c) resolving the effects of that blur on the image by solving an ill‐posed inverse problem using a spatially varying regularization term. The technique is demonstrated on synthetic examples and actual radiographs collected at the Naval Research Laboratory's (NRL) Mercury pulsed power facility.